Kuwait Finance House (M) Berhad, (KFHMB): Case Study Of Customers’ Acceptance Of The New Foreign Bank In Kuching / Zulkeplli Mohammad Nor - Mohammad Nor, Zulkeplli (2012)
Islamic Banks, like conventional banks, are profitable organizations. Their aim is to gain profit, but they are not allowed to deal with interest or to engage in any business or trade prohibited by Islam. In contrast, traditional conventional banks have their own main goal in the maximization of profit subject to a reasonable level of liquidity. They tend to deal with loans only and are keen in engaging themselves in direct investment as a main activity. The difference between the conventional banking system and the Islamic banking system is that, in the conventional system, interests are given (pre-promised) with a guarantee of repayment and a fixed percentage return while in the Islamic system, investors share a fixed percentage of profit when it occurs i.e. the share of the two practices will vary according to the profit achieved. Banks get back only a share of profit from the business to which it is a party and in case of loss, the business party loses none in terms of money but forgoes the reward for its activities during that period. According to Mckinsey (2008), Islamic finance has grown tremendously since it first emerged in the 1970's. Current global Islamic banking assets and assets under management have reached USD750 billion and is expected to hit USD1 trillion by 2010. Malaysia's long track record of building a successful domestic Islamic financial industry of over 30 years gives the country a solid foundation - financial bedrock ofstability that adds to the richness, diversity and maturity of the financial system. Presently, Malaysia's Islamic banking assets reached USD65.6 billion with an average growth rate of 18-20% annually.